Elderberry diet improves memory function and prevents cell death in rat models of Alzheimer’s disease induced by amyloid beta injection - Jahanbakhshi , Hadiseh; Irani , Shiva; Aliaghaei , Abbas (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: Alzheimer’s disease (AD) is a neurodegenerative disease which adversely affects memory and learning skills. Currently, there is no disease-modifying therapeutic approach for AD. Aim: A growing body of literature suggests elderberry as a promising remedy for neurological disorders. This study investigates the therapeutic effects of the elderberry diet on amyloid beta-induced (Aβ) rat model. Methods: Initially, Alzheimer’s model was generated by Aβ administration followed by the treatment of elderberry diet. Then, short term spatial memory was assessed. Stereology was also performed for the evaluation of density of neurons and dark neuron in the hippocampus. Results: The findings showed that the administration of the elderberry diet in an Aβ model of Alzheimer’ disease improved memory and learning function and prevented the degeneration of hippocampal neurons. Conclusion: Overall, the findings imply that the elderberry diet attenuates the Aβ-induced degeneration and improves memory performance. As such, the elderberry diet could be used as a therapeutic procedure for Alzheimer due to its neuroprotective effects.